Ash fusion behaviors of sugarcane bagasse and its modification with sewage sludge addition. (15th July 2022) - Li, Fenghai; Zhao, Chaoyue; Fan, Hongli; Xu, Meiling; Guo, Qianqian; Li, Yang; Wu, Lishun; Wang, Tao; Fang, Yitian
Abstract: The co-firing of sewage sludge and sugarcane bagasse (SB) is conducive to their environmentally benign reduction, reuse, and recycling. In this study, the ash fusion behavior of SB and its modification mechanisms by the addition of different sludges (municipal sewage sludge (MSS) and chemical industry sewage sludge (CSS)) were investigated using chemical composition calculations, mineral phase analysis, and thermodynamic calculations with FactSage. The slagging tendency of SB during the combustion process was high based on its ash composition and fusion index value. The ash fusion temperatures (AFTs) of the SB mixtures increased gradually with increasing sewage sludge percentage and this increased more obviously with the addition of CSS compared to MSS. This resulted from the difference in the decreasing non-binding/binding oxygen ratio. The generation of high melting point (MP) potassium aluminosilicates (e.g., KAlSi3 O8 and KAlSi2 O6 ) with the addition of sludge resulted in an obvious increase in the deformation temperatures of the SB mixtures. The formation of a small amount of high MP phosphates (e.g., Ca2.72 Mg0.28 (PO4 )2 ) resulted in a corresponding slow increase in the flow temperatures of the SB mixtures. Highlights: Sugarcane bagasse (SB) indicated high slagging tendency based on its ash composition. Ash fusion temperatures (AFTs) of SB mixtures increased with sewage sludge addition. Variations of non-binding oxygen/binding oxygen ratio illustrated their AFT change. Potassium aluminosilicate formation made deformation temperature obvious increase.